Factors Influencing the Purchase of Nipah Fruit Products: A Multiple Linear Regression Analysis - Felix Hisarma Lumban Gaol; Cut Gustiana; Supristiwendi Supristiwendi (JSEP (Journal of Social and Agricultural Economics), 2024)
Difficulties to develop into a problem that often occurs for business owners due to a lack of understanding of the factors that cause consumer behavior in the level of purchasing a product. This study aims to analyze the factors that influence the purchase of processed nipah fruit products at Bu Fitriani's nipah fruit soup business in Gampong Timbang Langsa, Langsa Baro District, Langsa City. The study used a causal design. The data collection method uses primary data and secondary data which are qualitative and quantitative in nature with the questionnaire measurement scale being a Likert scale. The population is all consumers and the sample was selected as many as 60 respondents using the incidental sampling method. The data analysis method uses multiple linear regression which is processed using IBM SPSS Statistic 22. The results showed a positive and significant effect of location, price perception, lifestyle and service on the level of purchase. Meanwhile, the diversity of products has a negative and insignificant effect on the level of purchase, which will later become an evaluation material to be improved so that the business can develop again in the future.